Pérmico continental en España. - Virgili, Carmen; Ramos, Amparo; Sopeña, A.; Hernando Costa, S. (Cuadernos de Geología Ibérica, 1977)
The present data show that the Spanish Permian is represented by the «Autunian» (Lower Rotliegendes) in a typical grey facies and redbeds similar to the «Saxonian» (Upper Rotliegendes). The Upper Permian has been found only in a very few points. In general it is made of detrital series, from clays to conglomerates; some volcaníc levels are found. Tickness is very variable, up to 2.000 meters. Sedimentation takes place in continental basins, tectonically con troled 1w the tardihercynian pbases. Their caracteristics and problenis are similar to the ones of Western European Permian. 1.